Answer :

Using Pythagoras triplets: (2m)2 + (m2 – 1)2 = (m2 + 1)2


2m = 4x


m = 2


m2 – 1 = (4-1)x = 3x


m2 + 1 = (4 + 1)x = 5x

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Write a PythagoreRS Aggarwal - Mathematics

The dimensions ofNCERT - Mathematics Exemplar

Find the length oNCERT - Mathematics Exemplar

Fill in the blankNCERT - Mathematics Exemplar

A 5.5 m long laddNCERT - Mathematics Exemplar

Can a right trianNCERT - Mathematics Exemplar

Which of the follRD Sharma - Mathematics

Write the PythagoNCERT - Mathematics Exemplar